Physical properties of aqueous blend of diethanolamine and sarcosine: Experimental and correlation study - Garg, S. (Springer International Publishing, 2017)
In this work, physical properties such as density, refractive index and viscosity of aqueous diethanolamine sarcosinate (DEA-SAR) solution were measured at different temperatures. The knowledge of physical properties is necessary for the process design and simulation of acid gas absorber plant. Various concentrations of aqueous DEA-SAR solutions (0.05, 0.10, 0.15, 0.20, 0.25 and 0.30) were investigated at temperature ranging from 298.15 to 333.15 K. The reported results showed an increment behavior in the physical properties with the increase in concentration isothermally, and a decreasing one with the rise in temperature of the solution at any given concentration. Empirical models were applied to correlate the experimental data of each physical property as a function of both concentration and temperature. A quantitative analysis of variation was carried out for estimating the significance of the physical property's data. © 2017 Institute of Chemistry, Slovak Academy of Sciences.